The Effects of Teacher Work Motivation and Teacher Professionalism on Instructional Quality in Public Elementary Schools in Banyuasin III District - Meri Susanti; Alhadi Yan Putra; Hery Setyo Nugroho (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study examined the effects of teacher work motivation and teacher professionalism on instructional quality in public elementary schools in Banyuasin III District. A quantitative ex post facto design was employed. The population consisted of 38 teachers from two public elementary schools, all of whom were included through total sampling. Data were collected using Likert-scale questionnaires and documentation. The instruments were valid and highly reliable, with Cronbach's alpha coefficients of 0.909 for teacher work motivation, 0.914 for teacher professionalism, and 0.891 for instructional quality. Data were analyzed through descriptive statistics, prerequisite tests, simple linear regression, and multiple linear regression using SPSS version 26. Teacher work motivation had a positive and significant effect on instructional quality (B = 0.306; t = 4.910; p < 0.001; R² = 40.1%). Teacher professionalism also had a positive and significant effect (B = 0.336; t = 4.329; p < 0.001; R² = 34.2%). Simultaneously, both variables significantly predicted instructional quality (F = 17.923; p < 0.001; R² = 50.6%), with the regression equation Y = 2.344 + 0.222X1 + 0.211X2. These findings show that instructional quality can be strengthened by sustaining teachers' work motivation and continuously developing their professional competence.